2021
DOI: 10.1073/pnas.2101674118
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fatty acid utilization increases chromatin oxidative stress in cardiomyocytes

Abstract: The inability of adult mammalian cardiomyocytes to proliferate underpins the development of heart failure following myocardial injury. Although the newborn mammalian heart can spontaneously regenerate for a short period of time after birth, this ability is lost within the first week after birth in mice, partly due to increased mitochondrial reactive oxygen species (ROS) production which results in oxidative DNA damage and activation of DNA damage response. This increase in ROS levels coincides with a postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The stimulation of cardiomyocyte regeneration post-cardiac injury is very challenging because cardiomyocytes quit the cell cycle shortly after birth, with no significant increase in cell number [ 19 ]. Different from other cell types, cardiomyocytes undergo a fundamental metabolic switch before and after birth; the primary energy resource of prenatal cardiomyocytes is provided by glycolysis, whereas postnatal cardiomyocytes rapidly shift to fatty acids oxidation as the primary energy source within days after birth [ 20 ]. Although many studies have investigated the importance of energy transition in cardiomyocytes [ 21 ], the mechanisms that lead to adult cardiomyocyte proliferation are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of cardiomyocyte regeneration post-cardiac injury is very challenging because cardiomyocytes quit the cell cycle shortly after birth, with no significant increase in cell number [ 19 ]. Different from other cell types, cardiomyocytes undergo a fundamental metabolic switch before and after birth; the primary energy resource of prenatal cardiomyocytes is provided by glycolysis, whereas postnatal cardiomyocytes rapidly shift to fatty acids oxidation as the primary energy source within days after birth [ 20 ]. Although many studies have investigated the importance of energy transition in cardiomyocytes [ 21 ], the mechanisms that lead to adult cardiomyocyte proliferation are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The gradual increase in oxygen levels immediately after birth is directly responsible for the switch from glucose to fatty acid metabolism and the inhibition of cardiomyocyte cell cycle activity through DNA damage in cardiomyocytes. [50][51][52][53] Moreover, hypoxemic cardiomyocytes in the adult mammalian heart, characterized by low capillary density surrounding them, are capable of proliferating even in adulthood 33 (Figure 1). Likewise, preserving hypoxic conditions after birth prolongs the proliferative state of cardiomyocytes.…”
Section: Metabolic Substratesmentioning
confidence: 99%
“…Shortly after birth, mammalian cardiomyocytes lose proliferative and regenerative capacities, highlighting a connection between metabolism and cardiac differentiation. The consequence of increased exposure to oxygen leads to an intensification of OXPHOS and increased levels of ROS [20], contributing to postnatal cardiomyocyte cell cycle arrest, oxidative DNA damage, and the activation of DNA damage response [102,103]. FA utilization by the mitochondria induces a significant increase in ROS at the chromatin level compared to other nuclear compartments, highlighting chromatin as the main target of the prooxidant effect of FA utilization by the mitochondria [103].…”
Section: Activation Of Cardiomyocyte Proliferationmentioning
confidence: 99%
“…The consequence of increased exposure to oxygen leads to an intensification of OXPHOS and increased levels of ROS [20], contributing to postnatal cardiomyocyte cell cycle arrest, oxidative DNA damage, and the activation of DNA damage response [102,103]. FA utilization by the mitochondria induces a significant increase in ROS at the chromatin level compared to other nuclear compartments, highlighting chromatin as the main target of the prooxidant effect of FA utilization by the mitochondria [103]. Puente et al investigated the influence of both hyperoxia and hypoxia in neonatal mice and reported that, while a high oxygen environment led to cardiomyocyte cell cycle arrest, lower oxygen extended the regenerative window [102].…”
Section: Activation Of Cardiomyocyte Proliferationmentioning
confidence: 99%